Analisis Perbedaan Return Saham dan Trading volume activity Sebelum dan Sesudah Stock split pada Perusahaan Go Public di BEI yang Melakukan Stock split Tahun 2017-2021 - Iqbal Wahyu Ilahi; Anik Malikah; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to determine the differences in stock returns and trading volume activity before and after the stock split in companies listed on the Indonesia Stock Exchange for the period 2017-2021. This study takes a sample of companies that did stock split listed in Indonesia Stock Exchange in year 2017-2021. The sample of this research is 34 of 40 companies that did stock split and fulfill the criteria’s that have been determined in 2017-2021. The sampling technique used is purposive sampling technique. This research uses paired sample t-test with 11 day of event period, which is 5 days before stock split (t-5) and 5 days after stock split (t+5). The result of the research showed that there was no difference between stock return before and after stock split. However, the second research indicates that stock split causes the difference of trading volume activity before and after stock split by company go public in Indonesia Stock Exchange in year 2017-2021.Keywords : Stock split, stock return, trading volume activity.